Near-room-temperature reversible giant barocaloric effects in [(CH3)4N]Mn[N3]3 hybrid perovskite. Issue 9 (7th October 2020) - Salgado-Beceiro, Jorge; Nonato, Ariel; Silva, Rosivaldo Xavier; García-Fernández, Alberto; Sánchez-Andújar, Manuel; Castro-García, Socorro; Stern-Taulats, Enric; Señarís-Rodríguez, María Antonia; Moya, Xavier; Bermúdez-García, Juan Manuel
Abstract : We report giant reversible barocaloric effects in [(CH3 )4 N]Mn[N3 ]3 hybrid organic–inorganic perovskite, near its first-order cubic-monoclinic structural phase transition at T 0 ∼ 305 K. Abstract : We report giant reversible barocaloric effects in [(CH3 )4 N]Mn[N3 ]3 hybrid organic–inorganic perovskite, near its first-order cubic-monoclinic structural phase transition at T 0 ∼ 305 K. When driving the transition thermally at atmospheric pressure, the transition displays a large change in entropy of ∼80 J K −1 kg −1 and a small thermal hysteresis of ∼7 K, as well as a large change in volume of ∼1.5%. When driving the transition with pressure near room temperature, the transition displays large changes in entropy of ∼70 J K −1 kg −1, which represent a giant barocaloric response. Hybrid perovskites with similar barocaloric response and lower operating temperatures may find applications in environmentally friendly cooling.